Fiscal Divergence and Current Account Imbalances in Europe - Gunther Schnabl; Timo Wollmershäuser (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Since the breakdown of the Bretton Woods System diverging current account positions in Europe have prevailed. While the Southern and Western European countries have tended to run current account deficits, the current accounts of the Central and Northern European countries, in particular Germany, have tended to be in surplus. The paper scrutinizes the role of diverging fiscal policy stances for current account imbalances in Europe since the early 1970s under alternative institutional monetary arrangements (floating exchange rates, European Monetary System, and European Monetary Union). It sheds light on the interaction of fiscal and monetary policies with respect to their impact on the current account and analyses the role of exchange rate changes and credit facilities as adjustment mechanisms for current account imbalances. Panel regressions reveal a robust impact of fiscal policy divergence on current account imbalances, which to a large extent is independent from the exchange rate regime, but which turns out to be contingent on the monetary policy stance.
Keywords: E62; E52; F32; 330